2019
DOI: 10.3390/bios9020069
|View full text |Cite
|
Sign up to set email alerts
|

Faecal Scent as a Novel Non-Invasive Biomarker to Discriminate between Coeliac Disease and Refractory Coeliac Disease: A Proof of Principle Study

Abstract: Currently, the gold standard for diagnosis of coeliac disease (CD) is based on serology and gastroduodenoscopy with histology of duodenal mucosal biopsies. The aim of this study was to evaluate the potential of faecal volatile organic compounds (VOCs) analysis as a novel, non-invasive tool to discriminate between CD in remission in patients on a gluten-free diet (GFD), refractory coeliac disease (RCD) and controls without CD. Patients with an established diagnosis of CD on a GFD, RCD and healthy controls (HC) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 39 publications
0
18
0
Order By: Relevance
“…Rouvroye et al [ 2 ] investigated the potential for analyzing the VOC profiles from stool samples of pediatric CD patients and healthy controls by means of GC-IMS, to determine the usefulness of this technique for the differentiation of RCD from CD, and to assess fecal VOCs as potential chemical biomarkers for RCD II. The study revealed no significant differences between fecal VOC-profile patterns of RCD from healthy controls, based on relatively small sample size used in this pilot study.…”
Section: Review Of Special Issue Contributionsmentioning
confidence: 99%
“…Rouvroye et al [ 2 ] investigated the potential for analyzing the VOC profiles from stool samples of pediatric CD patients and healthy controls by means of GC-IMS, to determine the usefulness of this technique for the differentiation of RCD from CD, and to assess fecal VOCs as potential chemical biomarkers for RCD II. The study revealed no significant differences between fecal VOC-profile patterns of RCD from healthy controls, based on relatively small sample size used in this pilot study.…”
Section: Review Of Special Issue Contributionsmentioning
confidence: 99%
“…Then, two different classifiers, specifically Random Forest and Gaussian process, were applied. These have previously been found to be good classifiers for GC-IMS data 46,47 . Once the training models have been created, they were applied to the same features in the test set.…”
Section: Methods Test Methodsmentioning
confidence: 83%
“…GC-IMS instrument (Dortmund, Germany), which is based on Gas Chromatograph – Ion Mobility Spectrometery principles (GC-IMS). This is a highly sensitive odour detection technology that has been previously used by our group in clinical studies analysing a range of biological samples 46 , 47 . In brief, the GC front end is used to pre-separate molecules based on their interaction with a stationary phase coating on a long column, eluding from the column at different times.…”
Section: Methodsmentioning
confidence: 99%
“…The data was analysed using the statistical pipeline successfully used in [16][17][18]. In summary, the GC-IMS data was first extracted using the L.A.V.…”
Section: Discussionmentioning
confidence: 99%
“…Here a Gas Chromatograph-Ion Mobility Spectrometer (GC-IMS) was used. Our group have previously used this instrument on a range of medical conditions including respiratory tract infections, Coeliac's disease and irritable bowel disease [16][17][18]. This instrument was chosen over more traditional gas chromatograph mass spectrometer (GCMS) as the basic sensitivity of the instrument is much higher than GCMS, it can use nitrogen/air as the carrier gas (so no need for expensive carrier gases such as helium), has a lower purchase/test cost than GCMS and has a much smaller form factor, making it applicable for a ward setting.…”
Section: Chemical Analysermentioning
confidence: 99%